Assuring the Quality of Essential Medicines Procured with Donor Funds - Moore, Thomas; Lee, David; Konduri, Niranjan; Kasonde, Lombe (World Bank, Washington, DC, 2013)
The donor community spends millions of dollars annually on procuring essential medicines as part of development assistance for health. Defining and enforcing quality standards for these medicines continues to prove challenging as this involves complex regulatory processes. While developed countries with stringent regulatory authorities in place have the capacity to comply with strict regulatory requirements, the essential medicines procured for developing countries are either not available in developed country markets, or are not the most competitively priced medicines internationally. Donors have therefore been forced to independently develop systems to purchase at lowest feasible cost, essential medicines for the developing world without compromising quality. Through a desk review and consultation with key stakeholders, this paper compiles data on various approaches used by international agencies and donor bodies to improve the quality of essential medicines they procure, beyond the World Health Organization (WHO) prequalification of medicines program and the global fund expert review panel, which focus only on medicines for treating HIV/AIDS, tuberculosis, and malaria. This paper additionally explores pragmatic options for a harmonized approach to ensuring the quality of medicines procured with donor funds. Based on the observed limitations of existing approaches, this paper considers a risk-based approach initiated by WHO, through which medicines in the WHO model list of essential medicines are classified according to risk categories (high, medium, and low). In the long run, the goal of international donor aid is to build the capacity of developing countries to take the lead in assuring the health of their citizens. Effective harmonization, coordination, and optimal leveraging of existing approaches may help national regulatory authorities to strengthen their own capacity to better control their markets, including registering products according to stringent standards, improving domestic manufacturing where applicable, and enhancing post-marketing surveillance.